Sex pheromone and period gene characterization of Lutzomyia longipalpis sensu lato (Lutz & Neiva) (Diptera: Psychodidae) from Posadas, Argentina - Salomón, Oscar Daniel (2010)
Lutzomyia longipalpis s.l. is the primary vector of Leishmania (L.) infantum in the New World. In this study, male Lutzomyia longipalpis specimens from Posadas, Argentina were characterized for two polymorphic markers: The male sex pheromone and the period (per) gene. The male sex pheromone was identified as (S)-9-methylgermacrene-B, the same compound produced by Lu. longipalpis from Paraguay and many populations from Brazil. The analysis of per gene sequences revealed that the population from Argentina is significantly differentiated from previously studied Brazilian populations. Marker studies could contribute to the understanding of the distribution and spread of urban American visceral leishmaniasis, thus aiding in the design of regional surveillance and control strategies.